Impact of phosphorus and luminosity on the propagation, photochemical reactions and quality of Lippia alba (Mill.) N.E.Br. seedlings - Santos, Cleberton Correia; Franco-Rodriguez, Alejandro; Araujo, Gonzalo Manuel; Scalon, Silvana de Paula Quintão; Vieira, Maria do Carmo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Lippia alba (Mill.) N.E.Br. (lemongrass) is a spice and medicinal plant species, with fledgling studies related to mineral nutrition and luminosity on foliar and vegetative responses. Thus, the aim of this study was to assess the foliar aspects and production of L. alba under two light conditions (full sun and 50% shading ) and four levels of phosphorus-P (0, 150, 300 and 450 mg kg-1). The L. alba seedlings presented changes in physiological indices and photochemical responses based on chlorophyll-a fluorescence. The phosphate fertilization helped mitigate the light stress for the synthesis of chlorophylls. The greatest leaf biomass production occurred with addition of P. The principal components analysis explained 74% of the variability, with leaf number, initial fluorescence and specific leaf area in principal component 1 (PC 1) and bud number, survival and leaf area in PC 2. Two groups formed in the cluster analysis, with lower distances between P300 full sun and P450 shading (2.31). The seedlings cultivated under full sun presented a higher survivability and seedling quality. The production of L. alba seedlings should be done under full sun with the addition of 450 mg kg-1 of phosphorus.